(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hassan NHM, Abdullah N, Kelana DNA, Perumal M. 2022. Early field growth performance of ten selected bamboo taxa: The case study of Sabal bamboo pilot project in Sarawak, Malaysia. Biodiversitas 23: 2882-2892. Information on early growth performance and survival rate of bamboos are pivotal for the development of the Sarawak bamboo industry. Thus, a study on the early growth performance of ten bamboo taxa was conducted at the Sarawak Bamboo Pilot Project site in Sabal, Simunjan, Sarawak, Malaysia. Six taxa were originated from Yogyakarta, Indonesia, and the other four bamboo taxa were originated locally from Sarawak. Study sites were established at bamboo plantation areas at different age stands. Two replications of data for each taxon involving 50 readings (25 readings for one replication) were measured and quantified for growth parameters of the number of culms per clump, number of new shoots, culm diameter, and culm height. The findings indicated that Gigantochloa hasskarliana (Busi bamboo) had the highest number of culms per clump (43) while Guadua angustifolia (Duri bamboo) had the highest number of new bamboo shoots (2.93). Nonetheless, Dendrocalamus asper (Green) had the highest culm diameter (3.61 cm) while Bambusa balcooa (Bema bamboo) had the highest culm height (8.36 m). The results showed that different bamboo species have different early growth performances, thus further detailed investigation and long-term monitoring period are required to achieve the commercial plantation scale, especially in Sarawak.